Burden of lower respiratory infections in five East Asian countries from 1990 to 2021: observation, comparison, and forecast from the global burden of disease study 2021 - Wang, Shiwei; Lin, Shuai; Zhong, Guodong; Qi, Zhangyang; Wang, Wei; Wen, Wen (Frontiers in Public Health, 2025)
ObjectiveLower respiratory infections (LRIs) remain a major global health challenge. Although the overall burden has declined, cross-country differences in long-term trends, age–sex patterns, and risk factors in East Asia are not well characterized. This study provides the first systematic comparison of long-term LRI trends across five East Asian countries—China, Japan, Republic of Korea, Democratic People’s Republic of Korea, and Mongolia—using Global Burden of Disease Study 2021 (GBD 2021) data.MethodsWe analyzed LRI incidence, mortality, and disability-adjusted life years (DALYs) from 1990 to 2021. Temporal trends were quantified by estimated annual percentage change (EAPC). We combined decomposition analysis and autoregressive integrated moving average (ARIMA) forecasting to quantify the relative contributions of population growth, aging, and epidemiological changes, and to project future trajectories. Risk factor attribution was evaluated using population-attributable fractions, and age–sex patterns were compared across countries.ResultsFrom 1990 to 2021, all five countries showed substantial reductions in age-standardized incidence and mortality, with Mongolia and China achieving the steepest declines. The burden shifted from children under five to older adults, particularly those aged ≥70 years, a novel epidemiological transition most evident in Japan and Korea. Decomposition indicated that epidemiological improvements were the primary drivers of mortality reductions, while population aging in Japan and Korea partially counteracted these improvements. Forecasts suggest continued declines in incidence and mortality across most countries, though Japan may experience a plateau in mortality.ConclusionThis study provides the first systematic comparison of long-term LRI trends across five East Asian countries. While the overall burden has declined, population aging, air pollution, and smoking are emerging challenges. By combining decomposition and ARIMA forecasting, our findings highlight the shift from children to older adults and offer timely evidence for age-sensitive, country-specific interventions such as vaccination for older adults, environmental regulation, and tobacco control.